Technological Self-Help and Equality in Cyberspace - Chandler, Jennifer (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
New technologies challenge the law in many ways, for example, they extend one’s capacity to harm others and to defend oneself from harm by others. These changes require the law to decide whether we have legal rights to be free from those harms, and whether we may react against those harms extrajudicially through some form of self-help (e.g., self-defence or defence of third parties) or whether we must resort to legal mechanisms alone. These questions have been challenging to answer in the cyberspace context, where new interests and new harms have emerged. The legal limits on permissible self-defence have historically been a function of necessity and proportionality to the threat.However, this article argues that case law and historical commentary reveal that equality between individuals is also an important policy issue underlying the limits on self-defence. The use of technologies in self-defence brings the question of equality to the fore since technologies may sometimes neutralize an inequality in strength between an attacker and a defender. A legal approach that limits resort to technological tools in self-defence would ratify and preserve that inequality.However, the relationship between technology and human equality is complex, and this article proposes an analytical structure for understanding it. The objective is to understand which technologies promote equality while imposing the least social costs when used in self-defence. The article proposes principles (including explicit consideration of the effects on equality) for setting limits on technological self-help, and illustrates their use by applying them to several forms of cyberspace counter-strikes against hackers, phishers, spammers, and peer-to-peer networks.